Higher-Order Chromatin Regulation of Inflammatory Gene Expression - Jin-Wen Xu; Shuang Ling; Jun Liu (Mediators of Inflammation)
Whether it is caused by viruses and bacteria infection, or low-grade chronic inflammation of atherosclerosis and cellular senescence, the transcription factor (TF) NF-κB plays a central role in the inducible expression of inflammatory genes. Accumulated evidence has indicated that the chromatin environment is the main determinant of TF binding in gene expression regulation, including the stimulus-responsive NF-κB. Dynamic changes in intra- and interchromosomes are the key regulatory mechanisms promoting the binding of TFs. When an inflammatory process is triggered, NF-κB binds to enhancers or superenhancers, triggering the transcription of enhancer RNA (eRNA), driving the chromatin of the NF-κB-binding gene locus to construct transcriptional factories, and forming intra- or interchromosomal contacts. These processes reveal a mechanism in which intrachromosomal contacts appear to be cis-control enhancer-promoter communications, whereas interchromosomal regulatory elements construct trans-form relationships with genes on other chromosomes. This article will review emerging evidence on the genome organization hierarchy underlying the inflammatory response.